2013
DOI: 10.1002/asia.201300106
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Benzotrifuran and Benzotripyrrole Derivatives and Molecular Orientations on the Surface and in the Solid State

Abstract: We developed a concise synthetic method for benzotrifurans and benzotripyrroles from 1,3,5-triethynyl-2,4,6-trifluorobenzenes by one-pot reactions in good to excellent yield. By investigating 2-D and 3-D structures of a variety of benzotrifuran and benzotripyrrole derivatives using scanning tunneling microscopy (STM) and single-crystal X-ray diffraction techniques, we found both similarities and dissimilarities. We also found that diverse molecular 3-D orientations were derived in their single crystals accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…The synthetic methodology followed together with the experimental details is given in the Supporting Information. Triple cyclization reactions were employed for the preparation of the BTP, BTF, and BTSe cores, according to the expeditious synthetic route previously reported by Nakamura and co‐workers and Takimiya and co‐workers . The desired BTP‐1 and BTF‐1 HTMs were successfully furnished as stable solids in 66 and 68% yields, respectively, by threefold Buchwald–Hartwig amination reactions with p ‐methoxydiphenylamine.…”
Section: Resultsmentioning
confidence: 99%
“…The synthetic methodology followed together with the experimental details is given in the Supporting Information. Triple cyclization reactions were employed for the preparation of the BTP, BTF, and BTSe cores, according to the expeditious synthetic route previously reported by Nakamura and co‐workers and Takimiya and co‐workers . The desired BTP‐1 and BTF‐1 HTMs were successfully furnished as stable solids in 66 and 68% yields, respectively, by threefold Buchwald–Hartwig amination reactions with p ‐methoxydiphenylamine.…”
Section: Resultsmentioning
confidence: 99%
“…Tsuji and co‐workers have reported a concise one‐pot synthesis of benzotrifurans and benzotripyrroles from 1,3,5‐triethynyl‐2,4,6‐trifluorobenzenes derivatives in good yields. But the reaction requires conditions with a high reaction temperature for satisfactory yields and benzo[ b ]thiophenes were not obtained in this reaction …”
Section: Figurementioning
confidence: 99%
“…There were slight increases in the driving voltage (7.4 V) and lower efficiencies (Z 1000 = 6.1 lm W À1 , EQE = 4.5%), which was possibly caused by the difference of molecular packing. 24 In a similar vein, a similar device using PhCZBDF (having a heterolytically stable phenylfuryl bond) has a very long lifetime of 44000 h. 19 In conclusion, we have shown that the hydrogen/deuterium exchange of a heterolytically labile C-H bond in an OLED host material increases the lifetime of the device. The deuterium atoms in CD 3 CZBDF did not change the device performance much except for the lifetime (and the maximum luminance which is related to the lifetime), because the photophysical and electrical processes as well as morphological changes do not include C-H(D) bond cleavage (cf.…”
mentioning
confidence: 69%